Multiple resonance type thermally activated delayed fluorescence by dibenzo [1,4] azaborine derivatives - Bae, Jaehyun; Sakai, Mika; Tsuchiya, Youichi; Ando, Naoki; Chen, Xian-Kai; Nguyen, Thanh Ba; Chan, Chin-Yiu; Lee, Yi-Ting; Auffray, Morgan; Nakanotani, Hajime; Yamaguchi, Shigehiro; Adachi, Chihaya (Frontiers in Chemistry, 2022)
We studied the photophysical and electroluminescent (EL) characteristics of a series of azaborine derivatives having a pair of boron and nitrogen aimed at the multi-resonance (MR) effect. The computational study with the STEOM-DLPNO-CCSD method clarified that the combination of a BN ring-fusion and a terminal carbazole enhanced the MR effect and spin-orbit coupling matrix element (SOCME), simultaneously. Also, we clarified the second triplet excited state (T2) plays an important role in efficient MR-based thermally activated delayed fluorescence (TADF). Further, we obtained a blue-violet OLED with an external EL quantum efficiency (EQE) of 9.1%, implying the presence of a pronounced nonradiative decay path from the lowest triplet excited state (T1).